A sonoelectrochemical preparation of graphene nanosheets with graphene quantum dots for their use as a hydrogen peroxide sensor. (20th January 2018) - Liu, Zhe-Ting; Ye, Jyun-Sian; Hsu, Su-Yang; Lee, Chien-Liang
Abstract: A sonoelectrochemical method has been successfully developed for the preparation of graphene nanosheet (GN)-supported graphene quantum dots (GN/GQDs) whereby sodium n-octyl sulfate intercalates into the interlayer spaces of a graphite working electrode under the combined effect of an applied potential and acoustic vibration power (640 W). GNs containing only pores can be prepared by lengthening the carbon chain of sodium n-alkyl sulfate (SCx S, x = 10, 12, and 14). Raman and X-ray photoelectron spectroscopic analyses and electrochemical analysis show that the densities of the structural defects on the GN/GQDs and different GNs and their responding activities for H2 O2 reduction are dependent on the carbon chain length of SCx S. These GN/GQDs have been used as non-enzymatic sensors for the determination of H2 O2 . Graphical abstract: Image 1 Highlights: A sonoelectrochemical method is developed for preparing GN/GQDs. SC8 S intercalates into graphite electrode under 640 W of acoustic vibration power. The various sodium n-alkyl sulfate for preparing GN/GQDs and GNs is studied. GN/GQDs have been used as electrochemical H2 O2 sensor.